Barbarians in Greek comedy - Long, Timothy, 1943- (Southern Illinois University Press, 1986)
"Greeks divided the world into Greece vs. the land of foreigners, into Hellenes vs. barbarians, seeing their country as a basƯtion of culture, learning, and military might surrounded by a sea of the unƯcivilized. Long shows how comedy expressed the Greek feeling of superiority over the barbarians, how it dealt with the so-called barbarian-Hellene antithesis. The result is a contribution to the study of ancient Greek comedy--both the comƯedy itself and the beliefs, the prejudices, the limitations, and the variety in the society from which the plays emerged. The comedians' responses to the barbarƯians ranged from idealization to neutralƯity to raw racism. Although contemptuous of barbarians, the Hellenes could not keep elements of foreign culture from entering their own. Long's major contention is that the Greek reaction to Asian and other foreƯign influence can be seen in the treatƯment of barbarians in Greek comedy."--Adapted from Amazon.com